Blood donation awareness among university students in Haryana: A cross sectional study. - Dipiya Tikoo, Shujaat Khan, Shahnaz Parveen, Rizni Mansoor (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Blood donation is a critical component of modern healthcare systems, yet many countries face chronic shortages due to low voluntary donation rates. University students represent a key demographic population for addressing this gap, but limited awareness and misconceptions often hinder participation. Methods: A cross-sectional survey was conducted among 500 university students to assess their awareness, attitudes, and practices regarding blood donation. Data were collected using a structured 10-item questionnaire covering donation history, knowledge of eligibility, perceived barriers, willingness to donate, and perceived importance. Descriptive statistics and visual analyses were used to interpret the results. Results: A cross-sectional study involving 500 university students (mean age: 21.4 years) were examined for knowledge, attitudes, and practices related to blood donation. Of the participants, 53% were male and 47% female. Only 28% had ever donated blood, with most donating just once. While 64% were aware of blood donation eligibility criteria and 60% knew the minimum age requirement. Key barriers to donation included fear of needles (36%) and lack of information (30%). Despite this, 62% expressed willingness to donate if a drive was organized on campus, and 70% believed in health benefits of donating blood. Awareness was considered highly important by the majority, with 72% rating it 4 or 5 on a 5-point scale. Conclusion: Although blood donation rates remain low among university students, the findings reveal a strong potential for increased participation through targeted awareness programs and on-campus donation drives. Addressing informational gaps and dispelling myths may significantly improve voluntary blood donation rates in this population.